Strategi Human Resource Management dalam Menghadapi Hiring Freeze pada Perusahaan Pialang Asuransi: Suatu Systematic Literature Review - Savitri Sri Lestari; Sitti Rakhman (Jurnal Deliberatif, 2026)
Abstract This study examines Human Resource Management (HRM) strategies for responding to hiring freeze policies in insurance brokerage companies through a Systematic Literature Review (SLR). The review analyzes national and international scholarly publications issued between 2021 and 2026 using a structured process of literature identification, screening, quality assessment, and synthesis guided by the perspectives of Strategic Human Resource Management, the Resource-Based View, Human Capital Theory, and Dynamic Capabilities. The findings indicate that hiring freezes are commonly adopted to address economic uncertainty, accelerate organizational efficiency, and support digital transformation. Although this policy can reduce labor costs, it may also increase employee workload, weaken engagement, and limit organizational performance when not supported by effective HR practices. The literature consistently highlights strategic workforce planning, employee upskilling and reskilling, internal talent development, employee engagement initiatives, digital HR transformation, adaptive performance management, and succession planning as key strategies for sustaining organizational capability during recruitment restrictions. The review concludes that the effectiveness of a hiring freeze depends primarily on an organization's ability to maximize existing human capital rather than merely suspending external recruitment. Accordingly, HRM should function as a strategic business partner that strengthens organizational resilience, service quality, and long-term competitiveness within the insurance brokerage industry.